An introduction to molecular ecology - Beebee, Trevor J. C. (Oxford University Press, 2004)
Ecology -- the study of how individuals and species interact with their surroundings, and each other -- has been revolutionized by a new molecular approach to the subject. By using molecular, biological and molecular genetic techniques, ecological interactions can be investigated in more detail and with more accuracy than ever before. An Introduction to Molecular Ecology makes this fascinating area of research accessible to students for the first time. Beginning with the history of molecular ecology, involving the relationships between natural history, genetics and evolution, the book moves on to discuss the areas of molecular population genetics, phylogeography, and molecular ecology in conservation biology. These are just a few of the ten chapters, which are individually structured to include background information, uestions of interest, the underlying theory of the various molecular and analytical approaches, and a range of relevant examples. Two substantial appendices detail accounts of the main practical and analytical methods currently used in molecular ecology